The Impact of Chronotype on Adolescent Health and Behavior: A Scoping Review - Rohman, Atiqur; Nur Setiawati Dewi; Meira Erawati (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2024)
Adolescents exhibit varying sleep-wake behaviors influenced by a range of biological, social, and psychological characteristics. Many adolescents today tend to follow an evening chronotype, which has implications for their health and developmental processes. To date, there has been no specific review synthesizing evidence from studies on the health and behavioral risks associated with chronotype in adolescents. This study aims to identify recent evidence on the health and behavioral impacts of chronotype in adolescents. A scoping review approach was used. Literature sources were obtained through database searches including PUBMED, ScienceDirect, and Scopus. The inclusion criteria for article selection were: (1) articles published within the last 5 years; (2) written in English; (3) article topics related to the impact of chronotype on adolescents; and (4) full-text availability, original articles, and accessible sources. This study employed the framework developed by Arksey and O’Malley, consisting of the following steps: 1. Identifying the research question; 2. Identifying relevant studies; 3. Selecting research articles; 4. Charting the data; and 5. Collating, summarizing, and reporting the results. Based on the selected articles, the researchers classified the impacts of chronotype on adolescent health into three main aspects: physical, psychological, and health-related and social behaviors. Chronotype affects all dimensions of adolescent developmental processes.